2014
DOI: 10.1111/j.1532-950x.2014.12206.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Outcome, Complications and Disease Progression in 23 Dogs After Placement of Tracheal Ring Prostheses for Treatment of Extrathoracic Tracheal Collapse

Abstract: Treatment of severe cervical tracheal collapse with commercially-available extraluminal ring placement leads to an overall improvement in quality of life and good long-term results, with about one-third of dogs requiring continued medical management. Most dogs do not have clinical signs consistent with disease progression after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(49 citation statements)
references
References 18 publications
(81 reference statements)
2
47
0
Order By: Relevance
“…Migration of extraluminal tracheal ring prostheses has also been previously reported, but no prosthesis migration was observed in our study . Various mortality rates related to respiratory compromise after tracheal ring placement ranging from 9%–26% have been reported . In our study, 13 of the 54 (24%) dogs had died by the time of data collection (median follow‐up time, 30 months).…”
Section: Discussionsupporting
confidence: 66%
See 4 more Smart Citations
“…Migration of extraluminal tracheal ring prostheses has also been previously reported, but no prosthesis migration was observed in our study . Various mortality rates related to respiratory compromise after tracheal ring placement ranging from 9%–26% have been reported . In our study, 13 of the 54 (24%) dogs had died by the time of data collection (median follow‐up time, 30 months).…”
Section: Discussionsupporting
confidence: 66%
“…Retrospective analysis of CETP placement revealed favorable short‐ and long‐term outcomes in dogs with tracheal collapse. Recent studies have reported that 92%‐95% of dogs survived to discharge after the placement of C‐shaped tracheal rings . We reported that 98% of the dogs survived to discharge except for 1 death due to DIC 16 days after surgery.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations